Decoupling of body-plan diversification and ecological structuring during the Ediacaran–Cambrian transition: evolutionary and geobiological feedbacks - Mángano, M. Gabriela (The Royal Society, 2014)
The rapid appearance of bilaterian clades at the beginning of the Phanerozoic is one of the most intriguing topics in macroevolution. However, the complex feedbacks between diversification and ecological interactions are still poorly understood. Here, we show that a systematic and comprehensive analysis of the trace-fossil record of the Ediacaran–Cambrian transition indicates that body-plan diversification and ecological structuring were decoupled. The appearance of a wide repertoire of behavioural strategies and body plans occurred by the Fortunian. However, a major shift in benthic ecological structure, recording the establishment of a suspension-feeder infauna, increased complexity of the trophic web, and coupling of benthos and plankton took place during Cambrian Stage 2. Both phases were accompanied by different styles of ecosystem engineering, but only the second one resulted in the establishment of the Phanerozoic-style ecology. In turn, the suspension-feeding infauna may have been the ecological drivers of a further diversification of deposit-feeding strategies by Cambrian Stage 3, favouring an ecological spillover scenario. Trace-fossil information strongly supports the Cambrian explosion, but allows for a short time of phylogenetic fuse during the terminal Ediacaran–Fortunian.